Intracranial Hemorrhage Complicating Herpes Simplex Encephalitis on Antiviral Therapy: A Case Report and Review of the Literature - Ghada ElShimy; Christina Mariyam Joy; Fred Berlin; Waleed Lashin (Case Reports in Infectious Diseases)
Herpes simplex virus (HSV) encephalitis is the most common cause of nonendemic sporadic encephalitis in the USA. Decreased mortality with early treatment with acyclovir has been documented. Although common complications include cortical petechial hemorrhages, frank intracerebral hematomas are considered very rare. Only few cases have been reported in the literature. We report a case of HSV encephalitis complicated by intracerebral hemorrhage 12 days after initiation of acyclovir therapy.